Wheat Productivity: Role of Farmers’ Nutritional Status - Zia ud Din; Parvez Iqbal Paracha; Zahoor ul Haq; Zahoor Ahmad; Zara Khan; Muhammad Asif (Turkish Journal of Agriculture: Food Science and Technology)
This follow-up study was carried out to investigate association of wheat productivity with the nutritional status of farmers in an agricultural area of North West Pakistan. A total of 1200 small scale farmers were randomly recruited and screened for nutrition status. Total of 226 farmers were found malnourished. An equal number of well-nourished farmers were randomly selected; detailed data on wheat yield and relevant confounding factors were collected interviewing groups. Multivariate linear regression analysis was performed to identify factors in relation to wheat yield. Comparing to well-nourished, malnourished farmers were more likely to report less wheat yield. Agricultural predictors that independently and significantly explained variation in wheat production included crop rotation, sowing time, and per acre agricultural inputs. Farmers' nutritional status; and dietary patterns further increased variance in wheat yield. The study findings reaffirmed the importance of farmers' nutritional status in predicting wheat yield.